The Effect of Low-Impact Aerobic Exercise on Reducing Stress Levels in the Elderly - Pratiwi, Gilang Dwi; Lucya, Vita; Hadiyani, Wini (STIKep PPNI Jawa Barat, 2024)
Aims: Increasing a person's age results in a significant decline in body development, which is one of the causes of stress conditions in the elderly. In addition to a decrease in physical condition, the elderly who experience a decrease in social activities, one of which is the state of retirement. The elderly who used to work experienced drastic changes in their activities. There needs to be special treatment that can divert the stress experienced by the elderly rather not get worse. This study aims to identify the effect of low-impact aerobic exercise on reducing stress levels in the elderly. Methods: This research is a quasi-experimental research (One Group Pre-Post-test design), sampling using purposive sampling of 30 respondents. The population in this study is the elderly in the Antapani District. The measurement tool used is the PSS-10 (Perceived Stress Scale) questionnaire. Results: The research results show that the majority of respondents in this study were female, with an average age of 60 years. Then on the Wilcoxon test there is a difference in the average value of the pre-test and post-test and the difference is quite large. Conclusion: There is an effect of low-impact aerobic exercise on reducing stress levels in the elderly. Suggestion: It is hoped that this exercise will be carried out regularly once a week. This is because in addition to body fitness, and to eliminate boredom, it can also reduce stress in the elderly.